Predictive model of career success of young elite football players - Voja Milosavljević; Vladimir Kitanović; Miloš Milošević; Željko Rajković (Journal of Applied Sports Sciences, 2025)
Early identifi cation and selection of candidates with the potential to become elite players are among the most common concepts in modern football. The goal of this research is to evaluate the predictive value of a wide battery of tests measuring the anthropometric, motor, and psychological characteristics of young elite soccer players during their youth phase, and to construct an eff ective predictive model of career success based on the results obtained. Anthropometric, motor, and psychological characteristics of 111 football players-members of the national teams from U13 to U18 of the Federal Republic of Yugoslavia (comprising the Republic of Serbia and the Republic of Montenegro) at the time of initial data collection were retrospectively analyzed in relation to the career outcomes over a 23-year follow-up period, culminating with the offi cial retirement of the last participant.Quantifi ed data were processed using descriptive statistics, multivariate analysis of variance (MANOVA), and canonical discriminant analysis with the SPSS 20 software package. Limitations of this study include: the small number of top-class players, which limits the ability to draw general conclusions; player selection was done chronologically instead of biologically, there is a lack of transitive testing, the choice of players for the team is determined by the coach’s personal taste, the factors of the social environment that infl uenced players’ development are not known, and there are not enough similar studies for comparison. The principal fi nding of this study is the eff ective diff erentiation of participants into distinct categories based on their anthropometric, motor, and psychological characteristics. The predictive model, derived from these variables, demonstrated a high level of accuracy in classifying players according to their subsequent career success.